Many Different LINE-1 Retroelements Are Activated in Bladder Cancer - Whongsiri, Patcharawalai (Int J Mol Sci, 2020)
Human genomes contain about 100,000 LINE-1 (L1) retroelements, of which more than 100 are intact. L1s are normally tightly controlled by epigenetic mechanisms, which often fail in cancer. In bladder urothelial carcinoma (UC), particularly, L1s become DNA-hypomethylated, expressed and contribute to genomic instability and tumor growth. It is, however, unknown which individual L1s are activated. Following RNA-immunoprecipitation with a L1-specific antibody, third generation nanopore sequencing detected transcripts of 90 individual elements in the VM-Cub-1 UC line with high overall L1 expression. In total, 10 L1s accounted for >60% of the reads. Analysis of five specific L1s by RT-qPCR revealed generally increased expression in UC tissues and cell lines over normal controls, but variable expression among tumor cell lines from bladder, prostate and testicular cancer. Chromatin immunoprecipitation demonstrated active histone marks at L1 sequences with increased expression in VM-Cub-1, but not in a different UC cell line with low L1 expression. We conclude that many L1 elements are epigenetically activated in bladder cancer in a varied pattern. Our findings indicate that expression of individual L1s is highly heterogeneous between and among cancer types.